The prevalence of smartphone addiction and its correlation with depression among higher college of technology students, Oman - AL Mahrooqi, Adil M.; AL Agbari, Talal A.; AL Shidhani, Asma S. (International Journal of Research in Medical Sciences, 2020)
Background: The aim of this study is to identify the prevalence of smartphone addiction and its correlation with depression among Higher College of Technology students in Oman. Methods: A cross-sectional study was conducted in the Higher College of Technology, Oman. A self-reported questionnaire was distributed electronically to students between January and February 2017. The questionnaire contained a validated short version of the smartphone addiction scale (SAS-SV) and a validated Arabic version of the Patient Health Questionnaire-9 (PHQ-9), along with a single question to self-assess smartphone addiction. Results: With a response rate of 86.2%, a total of 376 students were considered, of whom 34.6% were males and 65.4% were females, with an overall mean age of 20.9 years. This study showed that the prevalence of smartphone addiction in the study population using the SAS-SV was 63.8%; 88.3% of students were using their smartphones for four hours or more per day and 80% had been using smartphones for more than four years. The overall depression rate was 32.2%. As the total depression score increased by 1 point, the smartphone addiction score increased by 0.428 points (p<0.005). The prevalence of smartphone addiction was 54.9% among those who had no depression, 80.3% among those who had mild depression, 75.9% among those who had moderate depression, and 96.2% among those who have severe depression (p<0.005). Conclusions: This study shows high smartphone addiction levels based on SAS-SV scores and found a significant positive correlation between smartphone addiction score and depression scores.